Transgenic Plants With An Appendix on Intellectual Properties & Commercialization of Transgenic Plants by John Barton - Galun, Esra Breiman, Adina (Imperial College Press, 1997)
Presenting the essence of transgenic plant production, this work includes reviews available methodologies. Chapters also cover transgenic plants which were produced for crop improvement and increased product yield.